The Theological Value of Al-Ma’un in Free Lunch Policy: An Islamic Ethical Perspective on Social Empowerment - Andifa Nurasyam Zuhdi (Universitas Muhammadiyah Malang, 2024)
Providing free lunches is one of the innovations to prepare Indonesia's golden generation. This policy focuses on improving the nutrition of children and pregnant women. By providing free lunches, it is hoped that it will have a domino effect on the community. Of course, this policy must also be based on the ethics that apply in Indonesia. The free lunch policy has also gone through a series of in-depth scientific studies. Of course, this research will have a significant positive impact on society, considering that there is still a lot of inequality and poverty in Indonesia. Programs that are classified as social policies in economics are usually called